E-045 The effect of liquid embolic agents on gamma knife radiosurgery dosimetry for arteriovenous malformations. (16th November 2010) - Jiang, T; Mamalui-Hunter, M; Rich, K; Dryzmala, R; Derdeyn, C
Abstract : Purpose: The effectiveness of gamma knife stereotactic radiosurgery to obliterate brain arteriovenous malformations (AVMs) may be diminished by the preoperative adjunctive use of endovascular liquid embolic agents. The purpose of the present investigation was to determine if commercially available liquid embolic agents reduce the radiation dose to the target owing to attenuation of the Co-60 beam. Method and materials: (1) The apparent linear attenuation coefficients for 120 keV to 140 keV x-rays in the embolized regions were retrieved from CT scans for several patients with AVM malformations who had undergone embolization procedures with liquid embolic agents for the purposes of reduction in nidal volume. Based on these coefficients and our virtual model of gamma knife with basic ray tracing, we obtained the path lengths and densities for the embolized regions. The attenuation of Co-60 beams was then calculated for various sizes and positions of AVM embolized regions and the number of beams used for treatment. (2) Published experiments for several high atomic number materials were used to estimate the effective Co-60 beam attenuation coefficients for N-butylcyanoacrylate (n-BCA, suspended in ethiodized oil) and ethylene-vinyl alcohol copolymer (EVOH, with suspended micronized tantalum powder) used in the AVM embolizations. The dose reduction during gamma knife radiosurgery was calculated based on the Co-60 energy attenuation coefficient. (3) Dose measurements were obtained in a phantom study with EVOH to confirm the estimates generated in the theoretical model described in (2) above. Results: Based on apparent CT (keV) attenuation coefficients, the cumulative effect of either of the embolic agents decreased the dose delivered in gamma knife radiosurgery from −8 to −15% in a theoretical mod. Using the effective attenuation coefficient for Co-60 energies in the dose calculation yielded a 0.2% dose reduction per beam and less than 0.01–0.2% dose reduction in total. These theoretical results were validated in a phantom study. Conclusion: Dose reduction due to attenuation of the Co-60 beam by the AVM embolization material is negligible for both n-BCA and EVOH, owing to the high energy Co-60 beam.